Laminar lesions in horses with systemic oxidative stress, committed by experimentally induced or naturally occurring gastrointestinal disorders - Laskoski, Luciane M.; Locatelli-Dittrich, Rosangela; Sousa, Renato S.; Brum, Juliana S.; Cristo, Thierry G.; Montiani-Ferreira, Fabiano; Beltrame, Olair C.; Valadï¿½o, Carlos A.A. [UNESP] (FapUNIFESP (SciELO), 2016)
Laminitis in horses can be associated with lesions in multiple organs secondary to sepsis. Twenty-one horses suffering from gastrointestinal disorders were used in the experiment; 7 horses with experimentally induced endotoxemia and intestinal ischaemia, and 14 horses suffering from naturally occurring colic syndrome. Tissue samples of lungs, liver, heart, brain, cerebellum and hoof laminar tissue were collected for histopathological and oxidative stress evaluation using nitrotyrosine and superoxide dismutase (SOD2) immunostaining. The horses were divided into two groups: the non-oxidative lesions group (NOLG), with 7 horses showing weak immunostaining in lungs, liver and kidney, and the oxidative lesions group (OLG), with 14 horses showing immunostaining indicating systemic oxidative stress in multiple organs. The horses from OLG showed increase of laminar lesions and SOD2 immunostaining in multiple organs when compared to the horses from the NOLG. No differences were found ln regard to laminar immunostaining by nitrotyrosine and SOD2 between experimental groups. It was concluded that systemic oxidative stress can be associated with the development of laminar lesions, and that the laminar tissue does not respond to oxidative stress with increase of SOD as occurs in other organs.
Keywords: Horses; Laminitis; Nitrotyrosine; Peroxynitrite; Sepsis; Superoxide dismutase